A Criminal Career Study of the Continuity and Discontinuity of Sex Offending during the Adolescence-Adulthood Transition: A Prospective Longitudinal Study of Incarcerated Youth. (9th November 2016) - Lussier, Patrick; Corrado, Raymond R.; McCuish, Evan
Abstract : Longitudinal research has seriously challenged assumptions that juvenile sex offenders (JSO) are characterized by high level of dangerousness, mental health problems, and crime specialization in sex offenses. The current study examines the longitudinal pattern of offending among a sample of JSO and a sample of juvenile nonsex offenders. The research design includes longitudinal data over a nine-year period allowing the examination of offending patterns and the crime mix from age 12 to age 23. The findings highlight that, while JSO are prone to persist offending in adulthood, there is limited continuity of sex offending. Further, the findings stress the importance of taking into account nonsexual juvenile delinquency, more specifically, youth violence, to make a better assessment of early adult offending outcomes of JSO.